Ventilator-associated pneumonia in Coronary Care Unit of a tertiary level hospital in Bangladesh: causative organisms and pattern of antibiotic sensitivity (Bangladesh Critical Care Journal, 2019)
Background: Ventilator-Associated Pneumonia (VAP) is a frequent nosocomial infection. The etiology of VAP varieswith different patient populations and types of critical care settings.Materials & methods: This prospective observational study was conducted at the Coronary Care Unit (CCU) ofIbrahim Cardiac Hospital & Research Institute from April 2016 to November 2016. Demographic details andincidence of VAP was recorded and analysed by appropriate statistical tests.Results: 52 patients required mechanical ventilation, of whom 19 (36.5%) developed VAP. 15 (78.9%) had early VAP,while 4 (21.2%) had late VAP. CPIS, Modified CPIS and APACHE II Score- all were significantly higher among thosewho developed VAP (p